Study on The Areal Sweep Efficiency and Water Breakthrough Time Prediction of Water Flooding in Carbonate Reservoirs - Na, Risu; Zhang, Yu; Guo, Sheng; Li, Changyong; Sun, Futing (Journal of physics. Conference series, 2024)
This study concentrates on the evaluation of areal sweep efficiency and the prediction of water breakthrough time in a representative medium-porosity, medium-high permeability thin carbonate reservoir, using the H oilfield in the Middle East as an example. Areal geological models, accounting for variations in high permeability streaks and regional heterogeneity, were established to study the impact of areal heterogeneity on the sweep coefficient and morphology of the water flooding front. The results revealed that areal heterogeneity significantly affects both the areal sweep efficiency and the morphology of the water flooding front. In models with high permeability streaks, a greater permeability ratio led to more uneven displacement in all directions, consequently, this resulted in a poorer overall development effect. Furthermore, regional heterogeneity was found to significantly impact sweep efficiency, the larger the area of relatively low permeability zones, the more severe the reduction in sweep efficiency and the overall injection production effect. A theoretical method for accurately predicting water breakthrough time was established based on the stream tube method. This method was applied to the H oilfield, which reduced the discrepancy between the predicted and actual breakthrough times, thereby confirming its feasibility. The novelty of this study lies in overcoming the limitations of the stream tube method and utilizing numerical simulation to calculate the areal sweep coefficient at the time of water breakthrough. This approach quantitatively characterized the affected streamline area, thereby enhancing the accuracy of water breakthrough time predictions. This research provides significant theoretical insights and practical references for understanding the areal sweep efficiency of thin carbonate reservoirs, predicting water breakthrough times, and optimizing injection production strategies.